Search for (sub)stellar Companions of Exoplanet Hosts by Exploring the Second ESA-Gaia Data Release - Michel, K.-U.; Mugrauer, M. (Frontiers in Astronomy and Space Sciences, 2021)
We present the latest results of an ongoing multiplicity survey of exoplanet hosts, which was initiated at the Astrophysical Institute and University Observatory Jena, using data from the second data release of the ESA-Gaia mission. In this study the multiplicity of 289 targets was investigated, all located within a distance of about 500\,pc from the Sun. In total, 41 binary, and 5 hierarchical triple star systems with exoplanets were detected in the course of this project, yielding a multiplicity rate of the exoplanet hosts of about 16\,%. A total of 61 companions (47 stars, a white dwarf, and 13 brown dwarfs) were detected around the targets, whose equidistance and common proper motion with the exoplanet hosts were proven with their precise Gaia DR2 astrometry, which also agrees with the gravitational stability of most of these systems. The detected companions exhibit masses from about 0.016 up to 1.66\,M$_\odot$ and projected separations in the range between about 52 and 9555\,au.